1993
DOI: 10.1002/jcb.240530416
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of the avian progesterone receptor and its candidate receptor binding factor (RBF‐1)

Abstract: An avian oviduct nuclear matrix protein in the 6-10 kDa size range has been implicated to function in the cell-free nuclear binding of the avian oviduct progesterone receptor (PR). This protein, termed the receptor binding factor-1 (RBF-1), has been purified and partially characterized [Schuchard et al.: Biochemistry 30:4535-4542, 1991]. This paper describes the immunohistochemical co-localization of the RBF-1 and PR in the avian oviduct cell nuclei and rat reproductive cell nuclei using antibodies directed sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…1B). This is in agreement with that described in several other avian species including the domestic fowl (Gasc et al, 1984;Zhuang et al, 1993) and quail (Pageaux et al, 1983;Tsutsui, personal communication). Furthermore, these findings are consistent with an earlier study in the ring dove showing the greatest binding of radiolabelled progesterone in anterior and posterior hypothalamic tissue (Balthazart et al, 1980).…”
Section: Immunolocalization Of Steroid Receptorssupporting
confidence: 92%
“…1B). This is in agreement with that described in several other avian species including the domestic fowl (Gasc et al, 1984;Zhuang et al, 1993) and quail (Pageaux et al, 1983;Tsutsui, personal communication). Furthermore, these findings are consistent with an earlier study in the ring dove showing the greatest binding of radiolabelled progesterone in anterior and posterior hypothalamic tissue (Balthazart et al, 1980).…”
Section: Immunolocalization Of Steroid Receptorssupporting
confidence: 92%
“…Using immunohistochemical techniques with antibodies against the purified RBF, the RBF was localized to the nuclei of selected cell types in certain avian and rat tissues (27,28). In similar studies, colocalizations of RBF and PR in the same cell types in the avian oviduct and rat reproductive organs were also shown.…”
mentioning
confidence: 65%
“…These data support that the RBF appears to be an essential protein component of progesterone receptor nuclear acceptor sites, or, at least, a component of a subset of these sites in the chromatin structure and that specific DNA elements may be required for these sites. Immunohistochemical staining showed that RBF was located in the nucleus and colocalized in cells that also expressed progesterone receptor, such as avian oviduct and rat reproductive tissues (18).…”
mentioning
confidence: 99%